2012
DOI: 10.1111/jce.12045
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Sinus Rhythm as Endpoint of Persistent Atrial Fibrillation Ablation

Abstract: If SR is achieved as endpoint of persistent and long-standing persistent AF ablation using a sequential ablation approach it is associated with the highest long-term single procedure success rate compared to AT or AF at the end of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 30 publications
5
47
1
Order By: Relevance
“…The significance of sustained spontaneous or induced atrial tachyarrhythmia at the end of ablation procedures remains undetermined with respect to its association with the underlying atrial arrhythmogenic substrate and prognostic value. Noninducibility of any atrial tachyarrhythmia is associated with an increased long-term procedural success rate 33 ; however, in the present study, achieving noninducibility was not predictive of risk of long-term recurrence. Likewise, spontaneous or induced AT after LA circumferential ablation has a positive predictive value of only 55% for recurrent AT during follow-up.…”
Section: Discussioncontrasting
confidence: 54%
“…The significance of sustained spontaneous or induced atrial tachyarrhythmia at the end of ablation procedures remains undetermined with respect to its association with the underlying atrial arrhythmogenic substrate and prognostic value. Noninducibility of any atrial tachyarrhythmia is associated with an increased long-term procedural success rate 33 ; however, in the present study, achieving noninducibility was not predictive of risk of long-term recurrence. Likewise, spontaneous or induced AT after LA circumferential ablation has a positive predictive value of only 55% for recurrent AT during follow-up.…”
Section: Discussioncontrasting
confidence: 54%
“…Compared with patients without AF termination, patients with AF termination had a shorter duration of continuous AF (12 [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The rate of AF termination was similar in patients with and without amiodarone at the time of the procedure (75% versus 81%, P=0.58). Mean procedural and RF durations for patients in whom termination of AF was achieved versus not achieved were 264±74 minutes versus 263±64 minutes (P=0.91) and 89±28 minutes versus 99±27 minutes (P=0.09), respectively.…”
Section: Index Procedural Datamentioning
confidence: 87%
“…3 Several studies have shown that termination is predictive for long-term maintenance of SR. [19][20][21][22]33 O'Neill et al reported lower recurrence rates in patients with AF termination during index procedure (5% versus 39%). Termination to SR being associated with the highest single procedure success rate compared with AT or AF at the end of the procedure (42% versus 13% and 25%) was shown by Ammar et al In contrast, Elayi et al noted no impact of termination on SR maintenance.…”
Section: Af Terminationmentioning
confidence: 99%
“…In contrast to ablation of PAF, in which the end point of electric isolation of the pulmonary veins (PVs) is recommended by the guidelines, the optimal end point of CA in the setting of persAF is still under debate. 3,[19][20][21][22] The stepwise ablation approach aiming at procedural AF termination was introduced by Haïssaguerre et al 10,23 in 2005. Long-term follow-up data on any ablation approach for persAF are limited.…”
mentioning
confidence: 99%